The procrastinating student - Ruiz Alva, César (2017)
This article reflects on a problem that is increasingly growing among students and that should be addressed as a whole by those who assume the responsibility of training the student in the field of Education. Here the procrastinator student is described as that of a person whose profile is weak as regards organization, self-discipline, and willpower. It is desired to draw attention to identify this type of student in time, providing various intervention strategies, so that they are worked mainly within the tutorial action and help them overcome their difficulties.